Front Cover: Intrinsically Chiral Twist‐Bend Nematogens: Interplay of Molecular and Structural Chirality in the NTB Phase (ChemPhysChem 6/2023). Issue 6 (14th March 2023) - Walker, Rebecca; Pociecha, Damian; Salamonczyk, Miroslaw; Storey, John M. D.; Gorecka, Ewa; Imrie, Corrie T.
Abstract : The Front Cover is a cartoon depiction of the formation of the heliconical chiral twist‐bend nematic phase (N*TB ) from its constituent bent molecules. The presence of a single enantiomer of the chiral, lactate‐based liquid crystal dimers biases the formation of helices with only one handedness, unlike in the conventional NTB phase, observed for achiral molecules, for which the left‐ and right‐handed helices are doubly degenerate. More information can be found in the Research Article by Rebecca Walker and co‐workers .